The History of Accounting: An International Encyclopedia. - Boer, Germain B.; Boatsman, James R. (The Accounting Review, 1996)
Abstract Reviews the book `The History of Accounting: An International Encyclopedia,' by Michael Chatfield and Richard Vangermeersch.